1992
DOI: 10.1111/j.1365-4362.1992.tb03517.x
|View full text |Cite
|
Sign up to set email alerts
|

“Two‐step” Pemphigus Induction by Ace‐inhibitors

Abstract: Pemphigus lesions appeared in a 58-year-old man who was taking captopril for his hypertension. Drug withdrawal resulted in complete remission of the eruption. The subsequent use of enalapril as an antihypertensive agent caused a recurrence of pemphigus lesions along with onset of itching and dermographism. Intercellular antibodies were not found. Discontinuance of enalapril therapy had no effect on the clinical course. Steroid treatment was needed to resolve the eruption. Recently repeated immunofluorescent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…Enalapril is known to induce pemphigus in some subjects [2, 3, 4]. The acantholytic potential of this drug, a non-thiol antihypertensive ACE inhibitor, has repeatedly been proven in vitro [1, 6, 7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enalapril is known to induce pemphigus in some subjects [2, 3, 4]. The acantholytic potential of this drug, a non-thiol antihypertensive ACE inhibitor, has repeatedly been proven in vitro [1, 6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been known to potentially induce pemphigus in genetically predisposed subjects [2, 3, 4]. The complex and still only partially understood action mechanism seems to be correlated with an inhibitory interference of the drug with keratinocyte-aggregating enzymes [4, 5, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Previous studies suggested that a number of different medications can induce pemphigus variants. These can be categorized into the following 3 main groups: (1) drugs containing a sulfhydryl radical, such as penicillamine 14 or captopril (an angiotensin-converting enzyme inhibitor) 15 ; (2) masked thiols that contain an S molecule and can be converted to a thiol, such as penicillin 16,17 ; and (3) nonthiol or other drugs such as cephalosporins. 18 It has been postulated that, in a case of an abortive form of pemphigus induced by protracted penicillin treatment, the probable trigger was actually penicillamine, which was formed by the metabolic breakdown of the penicillin molecule.…”
Section: Discussionmentioning
confidence: 99%
“…We examined all purchases of medications that were previously associated with pemphigus 15,16,19,20 during the 6 months before the date that the pemphigus was first diagnosed. These medications included penicillins, cephalosporins, angiotensinconverting enzyme inhibitors, dipyrone, phenobarbiturate, topical anti-inflammatory drugs, and nonsteroidal antiinflammatory medications.…”
Section: Exposure Datamentioning
confidence: 99%
“…As mentioned before, these widely prescribed antihypertensive agents (table 3) are capable of inducing pemphigus independently from the thiol group that features their progenitor captopril [17, 18, 19, 20, 21]. In particular, enalapril, a nonthiol drug, which in vitro shows an acantholytic potential tenfold greater than captopril [22], can in vivo induce true pemphigus [19]or even a subclinical form of the disease [23].…”
Section: Drug Intakementioning
confidence: 99%